2015
DOI: 10.1108/nfs-02-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of quality attributes of chicken tikka prepared from spent hen meat with lemon juice and ginger extract marination

Abstract: Purpose – The purpose of this study is to produce spent hen tikka of improved quality attributes using lemon juice and ginger extract marination. Design/methodology/approach – Three experimental groups were made: control group, 20 per cent lemon juice marinated group (LM) and 50 per cent ginger extract marinated group (GM). Boneless spent hen breast meat was cut into small cubes of one inch with the help of knife and kept in marinade sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 11 publications
3
14
0
Order By: Relevance
“…The degree of acidification of the muscle tissue affects the technological and sensory characteristics of meat, as well as the development of microflora and the intensity of autolytic processes and, consequently, the processing value of meat. The results of studies by many authors (Ergezer and Goke, 2011;Kumar et al, 2015;Kumar et al, 2017;Yusop et al, 2010;Serdaroğlu et al, 2007) show that the pH of marinated meat depends on the pH of the marinade, which was confirmed in the present author's study ( Table 1). The study by Kumar et al (2017) indicated that the low meat pH after marination has positive effects on the texture, increasing the water holding capacity and the moisture content.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The degree of acidification of the muscle tissue affects the technological and sensory characteristics of meat, as well as the development of microflora and the intensity of autolytic processes and, consequently, the processing value of meat. The results of studies by many authors (Ergezer and Goke, 2011;Kumar et al, 2015;Kumar et al, 2017;Yusop et al, 2010;Serdaroğlu et al, 2007) show that the pH of marinated meat depends on the pH of the marinade, which was confirmed in the present author's study ( Table 1). The study by Kumar et al (2017) indicated that the low meat pH after marination has positive effects on the texture, increasing the water holding capacity and the moisture content.…”
Section: Resultssupporting
confidence: 89%
“…Increase in the moisture content might be attributed to marinade absorption. Similar results were obtained by Kumar et al (2015) and Kumar et al (2017) for breast muscles of hens after the laying period marinated with the use of lemon juice. Meat with a higher water holding capacity loses less meat juice during heat processing, which results in a better juiciness (Yusop et al, 2010).…”
Section: Resultssupporting
confidence: 84%
“…Differences in marinade absorption could be due to the density of marinades, differences in the osmotic pressure exerted by different marinade solutions, and also the marinades' pH. Many authors [8,14,16,34,35] indicate that the acidity of marinated meat depends on the pH of the marinade, as confirmed in the present study. e pH value of raw pheasant breast muscles marinated with acid whey and buttermilk was significantly (p < 0.05) lower than that of those marinated with lemon juice.…”
Section: Resultssupporting
confidence: 81%
“…Diversity of convenience/ready-tocook/ready-to-serve chicken meat products such as kababs, tikkas, lollipops, fingers, nuggets, patties and sausages exist in the markets. However, perishability of meat products has been regarded as a very serious problem, particularly in tropical countries like India, where household refrigeration facility is scanty (Kumar et al, 2015). In the present era, development of safe and shelf stable products is the priority of food industry to curtail the high energy cost involved in food preservation and for consumer safety.…”
Section: Issn: 2319-7706 Volume 8 Number 02 (2019)mentioning
confidence: 99%